Estimation of CO2 Emissions in Incinerator by Actual Measurement and IPCC Guideline - Chung, Jin-Do; Dorjderem, Munkhbaatar; Hwang, Seung-Min (Asian Journal of Chemistry, 2013)
This research analyzed the emission factors of emission characteristics of incineration facilities of municipal solid waste and compared the results by different estimation methods, in order to suggest the emission amount estimation methods that occur in municipal solid waste. It can be understood that the total actually measured CO2 emission was shown low by comparison with emission amount by the IPCC guideline. For estimating the CO2 emission for biomass, the average amount of actually measured CO2 was also shown wide difference with the average emission amount by the estimation method suggested in the IPCC guideline. One of the reasons in these results is that it shows wide difference compared with estimation result by IPCC guideline because actual CO2 measurement in incinerator could be done only twice a year. Also, it is considered that the CO2 emission amount is rapidly increased owing to incineration of the food wastewater in the incinerator.